Nonlinear iterative methods for solving the split common null point problem in Banach spaces. (4th July 2019) - Suantai, Suthep; Shehu, Yekini; Cholamjiak, Prasit
ABSTRACT: In this work, we study the split common null point problem in the framework of Banach spaces. We propose an iterative scheme for solving the problem and then prove strong convergence theorem of the sequences generated by our iterative scheme under suitable conditions. We finally provide some numerical examples to support the main theorem.